Systemic markers of the redox balance and Apolipoprotein E Polymorphism in Atherosclerosis: the Relevance for an Integrated Study - Lopes, Paula Alexandra (2006)
Prospective studies have demonstrated that an imbalance between oxidative damage and antioxidative protection can play a role in the development and progression of atherosclerosis. Also, genotypes with the apolipoprotein E ζ4 allele have been associated with an increase risk for this pathology. Based on this knowledge, the aim of this study was to evaluate indicators of the redox balance, trace elements, and apolipoprotein E allelic profile in subjects from the Lisbon population with clinically stable atherosclerosis, at risk for atherosclerotic events, and in healthy subjects for comparison. The activities of superoxide dismutase in erythrocytes and glutathione peroxidase in whole blood, plasma total thiols, and serum ceruloplasmin were kept unchanged among the three groups. Serum α-tocopherol was increased in atherosclerotic patients. Total malondialdehyde in serum and protein carbonyls in plasma, which are indicators of lipid and protein oxidative damage, respectively, reached their highest values in risk subjects. The concentrations of potassium and calcium, in plasma and in blood cells, were slightly elevated in patients and might reflect an electrolytic imbalance. Regarding the apolipoprotein E polymorphism, atherosclerotic patients had an increased incidence of the high-risk genotypes for atherogenesis (ζ3/ζ4 and ζ4/ζ4). A multivariate model applied to the general population using most of the parameters clearly separated the three groups at study (i.e., the healthy group from the steady-state group of risk disease and from the atherosclerotic one). As shown by us, the usefulness of biochemical and complementary genetic markers is warranted for a better knowledge on atherosclerosis molecular basis.